Comparative Analysis of Supplier Selection Methods in Industry-Specific Contexts - Bányai, Ágota; Bányai, Tamás (Advanced Logistic Systems - Theory and Practice, 2025)
Supplier selection is a key strategic decision in logistics and supply chain management, directly influencing a company’s competitiveness, cost efficiency, and sustainability performance. This paper provides a comprehensive overview of the main criteria and methodological approaches applied in supplier evaluation. It explores the importance of financial, quality, delivery, compliance, sustainability, and communication factors, as well as their industry-specific adaptations in sectors such as automotive, food, pharmaceutical, electronics, construction, and textile manufacturing. The methodological section presents and compares several decision-making techniques (including the Datum, Dodgson, Plurality, Weighting, and Analytic Hierarchy Process (AHP) methods) highlighting their advantages, limitations, and suitability for multi-criteria decision environments. Finally, the study discusses emerging trends such as digitalization, data-driven evaluation, ESG considerations, and resilience-oriented supplier assessment, emphasizing the growing need for continuous and transparent supplier performance monitoring in modern logistics systems.